2022
DOI: 10.20473/mkh.v33i2.2022.96-104
|View full text |Cite
|
Sign up to set email alerts
|

Potensi Pemberian Probiotik Terhadap Peningkatan Berat Badan, Konsumsi, Dan Konversi Pakan Ayam Petelur Fase Pre Layer

Abstract: Probiotik adalah segala bentuk sediaan sel mikroba atau komponen sel mikroba yang mempunyai pengaruh menguntungkan bagi kesehatan dan kehidupan inangnya. Beberapa aditif pakan seperti hormon Antibiotik Growth Promoter (AGP) telah dilarang. Oleh karena itu, saat ini probiotik sering digunakan sebagai bahan tambahan pengganti antibiotik. Probiotik yang banyak digunakan adalah bakteri asam laktat karena dapat meningkatkan efisiensi pencernaan dan penyerapan nutrisi. Tujuan dari penelitian ini adalah untuk mengeta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…apart from being a crude fiber degrader, it can also increase feed digestibility. Probiotics in the digestive tract of chickens can increase nutrient digestibility, so that growth and feed efficiency can be optimal [31]. It was reported by [32] that probiotics can effectively improve broiler growth performance through modulating the beneficial microbiota in the caecum.…”
Section: Resultsmentioning
confidence: 99%
“…apart from being a crude fiber degrader, it can also increase feed digestibility. Probiotics in the digestive tract of chickens can increase nutrient digestibility, so that growth and feed efficiency can be optimal [31]. It was reported by [32] that probiotics can effectively improve broiler growth performance through modulating the beneficial microbiota in the caecum.…”
Section: Resultsmentioning
confidence: 99%
“…Probiotik yang banyak digunakan adalah bakteri asam laktat yang dapat meningkatkan kemampuan imunitas nonspesifik (Jannah et al 2022). Bakteri asam laktat yang memiliki sifat probiotik salah satunya adalah Lactobacillus plantarum IIA-1A5 yang diisolasi dari daging sapi Peranakan Ongole (PO) dan telah memenuhi syarat sebagai strain probiotik berdasarkan pengujian in vivo dan in vitro (Arief et al 2014).…”
Section: Pendahuluanunclassified
“…The average ration conversion value in this study indicated that probiotic supplementation in the diet tended to improve ration conversion values. Jannah et al [16] reported that improving the conversion value of the ration in chickens given the probiotic Bacillus sp. enabled the digestibility of feed ingredients to be more perfect.…”
Section: Egg Production Performancementioning
confidence: 99%